Green management interpretation within entrepreneurship framework - Khachatryan, Nonna (Bulletin of Yerevan University G: Economics, 2024)
Currently, organizations are trying to organize green business along with traditional entrepreneurship. Organizing a green business improves the organization’s competitive position in the market, but at the same time requires the existence of a balanced ecosystem, that promotes sustainable development. In this regard, it is important to assess the functioning of the green entrepreneurship ecosystem at the micro-level of the economy. The article clarifies the scope of the green entrepreneurship ecosystem of organizations and makes recommendations for the performance evaluation of its activities․